2019
DOI: 10.1038/s41388-019-0888-1
|View full text |Cite
|
Sign up to set email alerts
|

RNA splicing factor USP39 promotes glioma progression by inducing TAZ mRNA maturation

Abstract: Increasing evidence demonstrates that ubiquitin specific protease 39 (USP39) plays an oncogenic role in various human tumors. Here, using expression analysis of the publicly available Oncomine database, clinical glioma patient samples, and glioma cells, we found that USP39 was overexpressed in human gliomas. Knockdown of USP39 in glioma cells demonstrated that the protein promoted cell growth, invasion and migration in vitro and in a tumor model in nude mice. To identify mediators of USP39 growth-promoting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…The decreased levels of LATS1 unleash YAP activity and support pro-oncogenic features in glioma cells [74] (Table 2). In line with these observations, the splicing factor USP39 is up-regulated in high-grade gliomas [73], whereas reduced levels of LATS1 associate with poor prognosis in glioma patients [75]. Although the mechanisms driving these splicing-related events (i.e., up-regulation of USP39 and splicing of PMEPA1a) are still unknown, these studies suggest that splicing dysregulation impacts a key developmental program by altering the equilibrium of the Hippo pathway during gliomagenesis.…”
Section: Hippo Signaling Pathwaysupporting
confidence: 52%
See 1 more Smart Citation
“…The decreased levels of LATS1 unleash YAP activity and support pro-oncogenic features in glioma cells [74] (Table 2). In line with these observations, the splicing factor USP39 is up-regulated in high-grade gliomas [73], whereas reduced levels of LATS1 associate with poor prognosis in glioma patients [75]. Although the mechanisms driving these splicing-related events (i.e., up-regulation of USP39 and splicing of PMEPA1a) are still unknown, these studies suggest that splicing dysregulation impacts a key developmental program by altering the equilibrium of the Hippo pathway during gliomagenesis.…”
Section: Hippo Signaling Pathwaysupporting
confidence: 52%
“…Splicing factors can impact the expression of components of the Hippo pathway in brain tumors. For instance, the ubiquitin specific protease 39 (USP39), promotes RNA processing and expression of TAZ, thus favoring glioma oncogenic features in vitro and in vivo [73] (Table 2). Furthermore, recent evidence indicates that gliomas express high levels of a splice variant of the prostate transmembrane (TM) protein, androgen induced 1 (PMEPA1) called PMEPA1a, which promotes degradation of the tumor suppressor LATS1 protein.…”
Section: Hippo Signaling Pathwaymentioning
confidence: 99%
“…Previous studies have shown that attenuation in splicing factor-driven RNA maturation promotes tumorigenesis through the accumulation of pre-mRNAs 51,52 . We found decreased expression of KSR2 due to impairment in SF3B1-mediated mRNA maturation and KSR2 partially contributes to SF3B1 pro-proliferative function.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 hub genes expressed in lung cancer analyzed by Oncomine. To investigate the clinical significance of the hub genes, the expression of these 10 hub genes in lung cancer and normal tissues was analyzed with the Oncomine database 26,50,51 . A previous study (Bhattacharjee) 52 revealed that EGFR mRNA expression levels were significantly higher in squamous cell lung carcinoma than in lung (Fig.…”
Section: Survival Analysis Of Hub Genesmentioning
confidence: 99%